STUDENTS’ PERCEPTION OF MEDICAL PROFESSIONALISM - Cicih Bhakti Purnamasari; Fairuz Salsabila Faisal (Jurnal Ilmu Kesehatan, 2021)
Mastery of professionalism is a necessity in medical education. However, the application in education is still limited. Therefore, it is necessary to explore the definition of professionalism in the medical field. This study aimed to explore students' perceptions of medical professionalism, as well as the behavioral components that demonstrate professionalism. This was a qualitative analytic study, carried out among 2 focus group discussions (FGD) of students with a grounded theory approach in data analysis. The research was conducted at the Faculty of Medicine, Gadjah Mada University. Results showed that students' perceptions of medical professionalism included mastery of knowledge, skills, and overall attitudes. Meanwhile, the professionalism component consists of altruism, competence, honesty and integrity, performance, management, respect for others and humanism. Keywords: professionalism, medical professionalism